Standard: Human gastric organoids - Fan Hong; Ronghui Tan; Ting Wang; Nanshan Zhong; Hongling Zhao; Rui-hua Xu; Lin Shen; Yingbin Liu; Xuebiao Yao; Dongxi Xiang; Lijian Hui; Jianping Xiong; et al. (Cell Regeneration)
Abstract Organoid technology provides a transformative approach to understand human physiology and pathology, offering valuable insights for scientific research and therapeutic development. Human gastric organoids, in particular, have gained significant interest for applications in disease modeling, drug discovery, and studies of tissue regeneration and homeostasis. However, the lack of standardized quality control has limited their extensive clinical applications. The “Human Gastric Organoids” is part of a series of guidelines for human gastric organoids in China, which establishes comprehensive standards on terminology, technical specifications, testing methods, inspection rules, usage instructions, labeling, transportation, and storage, developed by experts from the Chinese Society for Cell Biology and its branch societies. Released on October 29, 2024, this guideline aims to establish standardized protocols, enhance institutional practices, and promote international standardization for clinical and research applications of human gastric organoids.